Difference in Secondary Effects Between AstraZeneca Vaccine and Sinovac Vaccine for Females Aged 18 and above in 2023 - Costa Monteiro, Ermelinda da; Costa Neto, Sandra da; Dionisio Ximenes, Jose; Conceição Matos, Livio da; Carvalho de Araújo, Eugenia; Soares Tilman, Etelvina Jose (Rifa'Institute, 2024)
Introduction: The COVID-19 pandemic has had a severe impact on health, economy, and society worldwide. According to WHO, COVID-19 vaccines are safe and effective in protecting individuals from the risk of severe COVID-19 disease and death. COVID-19 vaccines have received Emergency Use Listing (EUL) and Emergency Use Authorization (EUA) licenses. According World in Data, 53.8% of the global population has received the first dose of COVID-19 vaccination, with 7 million doses provided globally. Timor Leste has vaccine coverage of 78% and 65.1% for the first and second doses of AstraZeneca and 6.3% and 5.9% for Sinovac. Objective: To determine the difference in the secondary effects of AstraZeneca and Sinovac vaccines for females aged 18 or older in Becora village, Cristo Rei administrative post, Dili municipality, in the year 2023. Method: A quantitative analytical method with a cross sectional approach was used with a total sample population of 325 female respondents aged 18 or older who had received the AstraZeneca or Sinovac vaccines. Results and Discussion: Out of the 325 female respondents, 173 (53.2%) received the AstraZeneca vaccine, and 152 (46.8%) received the Sinovac vaccine. 142 (82.1%) of the AstraZeneca vaccine recipients and 92 (60.5%) of the Sinovac vaccine recipients experienced side effects classified as mild. 89 (51.4%) of the AstraZeneca vaccine recipients reported lower body pain. The Sinovac vaccine accounts for 44 (28.9%) of the total. The statistical test results show that there is a significant difference in secondary effects between the AstraZeneca and Sinovac vaccines (p value: 0.000) in cotton thread. The secondary effects in the body are different between the AstraZeneca and Sinovac vaccines (p value: 0.000). Conclusion: Based on the results from female respondents aged 18 and above who have received COVID-19 vaccines, it shows that there is a difference in secondary effects between the AstraZeneca and Sinovac vaccines.